Multidimensional Parity Algorithms to Escalate the Security of Intelligent Mobile Models in Education - R. Vidhya; T. Padmapriya; S. Selvakumar; R. Mary Victoria; M. Anand (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The traditional multiple reserves and resounding costs of increase of the corporal volume can be replaced by a distributed file model of divided data employing algorithms, multidimensional integrity, and resilience to complete losses of the storage facilities. The model’s created duplicated data enables you to recover some of the split components’ lost functionality. A rapid shift in the appraisal and application of knowledge is also required by increasing information and communication technologies. As a result, modern learning methodologies, approaches, and technologies are being developed. This paper describes how to build an automated instructional and analytical complex using semantic information. It has been established what is needed for such an educational and technological complex. Tools built on a semantic network are represented in formal and structural models. Since it was created using a thorough understanding of the topic, the model is intended to facilitate students’ perception of the many educational and technical complexities and to enhance the teacher’s work.